1997
DOI: 10.3171/foc.1997.2.4.7
|View full text |Cite
|
Sign up to set email alerts
|

The importance of pial blood supply to the development of peritumoral brain edema in meningiomas

Abstract: The authors studied the pial and dural blood supplies in 74 intracranial meningiomas and quantified their associated peritumoral brain edema (PTBE). The extent and localization of pial blush in relation to the total tumor volume were determined angiographically. The amount of edema and tumor size were calculated using computerized tomography. The edema-tumor volume ratio was defined as Edema Index (EI). There were 49 meningiomas with PTBE; of those tumors, 46 were supplied by pial vessels, and three we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 28 publications
(32 reference statements)
2
35
0
6
Order By: Relevance
“…9,10 However, more recent reports have demonstrated such a relationship. 6,7,10,11 In these reports, the meningothelial subtype was associated with PTBE more often than fibroblastic subtypes. In 1992, Inamura et al reported that meningothelial and transitional meningiomas tended to be associated with a larger area of PTBE than fibroblastic meningiomas.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…9,10 However, more recent reports have demonstrated such a relationship. 6,7,10,11 In these reports, the meningothelial subtype was associated with PTBE more often than fibroblastic subtypes. In 1992, Inamura et al reported that meningothelial and transitional meningiomas tended to be associated with a larger area of PTBE than fibroblastic meningiomas.…”
Section: Discussionmentioning
confidence: 91%
“…2 Although previous reports have found no relationship between tumor size and PTBE, as was the case in our study, 9,22 some authors have reported that larger tumor volume is related to the incidence of PTBE. 3,[5][6][7][8]11,14 Several authors have reported that frontal sphenoid ridge meningiomas are associated with increased PTBE in comparison with those in other areas. 22,24 This is contrary to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meningiomas with a blood supply of exclusively dural origin are typically free from edema, whereas communication between the tumoral blood supply and the cerebral circulation is generally accompanied by the development of edema [44]. A connection between the tumoral blood supply and the cerebral circulation demonstrates the close morphological relationship of the tumor surface and the adjacent brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changes in the arterial blood supply of tumors indicate the significance of the brain-tumor interface [41,44]. Meningiomas with a blood supply of exclusively dural origin are typically free from edema, whereas communication between the tumoral blood supply and the cerebral circulation is generally accompanied by the development of edema [44].…”
Section: Discussionmentioning
confidence: 99%